Age effects on cognitive functions and speech-in-noise processing: An event-related potential study with cochlear-implant users and normal-hearing listeners - Burkhardt, Pauline; Müller, Verena; Meister, Hartmut; Weglage, Anna; Lang-Roth, Ruth; Walger, Martin; Sandmann, Pascale (Frontiers in Neuroscience, 2022)
A cochlear implant (CI) can partially restore hearing in individuals with profound sensorineural hearing loss. However, electrical hearing with a CI is limited and highly variable. The current study aimed to better understand the different factors contributing to this variability by examining how age affects cognitive functions and cortical speech processing in CI users. Electroencephalography (EEG) was applied while two groups of CI users (young and elderly; N = 13 each) and normal-hearing (NH) listeners (young and elderly; N = 13 each) performed an auditory sentence categorization task, including semantically correct and incorrect sentences presented either with or without background noise. Event-related potentials (ERPs) representing earlier, sensory-driven processes (N1-P2 complex to sentence onset) and later, cognitive-linguistic integration processes (N400 to semantically correct/incorrect sentence-final words) were compared between the different groups and speech conditions. The results revealed reduced amplitudes and prolonged latencies of auditory ERPs in CI users compared to NH listeners, both at earlier (N1, P2) and later processing stages (N400 effect). In addition to this hearing-group effect, CI users and NH listeners showed a comparable background-noise effect, as indicated by reduced hit rates and reduced (P2) and delayed (N1/P2) ERPs in conditions with background noise. Moreover, we observed an age effect in CI users and NH listeners, with young individuals showing improved specific cognitive functions (working memory capacity, cognitive flexibility and verbal learning/retrieval), reduced latencies (N1/P2), decreased N1 amplitudes and an increased N400 effect when compared to the elderly. In sum, our findings extend previous research by showing that the CI users’ speech processing is impaired not only at earlier (sensory) but also at later (semantic integration) processing stages, both in conditions with and without background noise. Using objective ERP measures, our study provides further evidence of strong age effects on cortical speech processing, which can be observed in both the NH listeners and the CI users. We conclude that elderly individuals require more effortful processing at sensory stages of speech processing, which however seems to be at the cost of the limited resources available for the later semantic integration processes.